2016
DOI: 10.1589/jpts.28.2190
|View full text |Cite
|
Sign up to set email alerts
|

Association of neuropathic pain with ultrasonographic measurements of femoral cartilage thickness and clinical parameters in patients with knee osteoarthritis

Abstract: [Purpose] The aim of this study was to investigate whether neuropathic pain is associated with femoral condylar cartilage thickness, electrical pain threshold, and clinical parameters in patients with knee osteoarthritis. [Subjects and Methods] Sixty patients over the age of 40 diagnosed with knee osteoarthritis were enrolled. The PainDETECT questionnaire, Western Ontario and McMaster Universities Osteoarthritis Index, Hospital Anxiety and Depression Scale, and Short Form-36 questionnaire were completed for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
1
17
1
1
Order By: Relevance
“…Neuropathic pain exerts a negative impact on the quality of life and functional status of patients with pain. 6,8,16,17 In this study, quality of life and depression there was no difference between groups with regard to.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Neuropathic pain exerts a negative impact on the quality of life and functional status of patients with pain. 6,8,16,17 In this study, quality of life and depression there was no difference between groups with regard to.…”
Section: Discussionmentioning
confidence: 55%
“…8,19 In the present study, 38.52% of the patients had neuropathic pain. Pain detection scoring was used in previous studies to identify neuropathic pain in knee OA, and the neuropathic pain ratio was 17.6% accord-ing to Ohtori et al and 46.7% by Mesciet al, 26.7% by Rienstra et al 16,17,20 Although such studies identified the neuropathic pain ratio, varying number of patients and use of different scales might be the basis for the difference in results. Askin et al used both pain detection and DN4 scale for detecting neuropathic pain in 60 patients, which identified 66.7% and 46.7%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…The relationship between the neuropathic pain component in knee OA and age, symptom duration, and radiological severity of OA are among the current topics of investigation. Ohtori et al [32] and Mesci et al [35] found no relationship between PainDETECT score and age, symptom duration, and radiological grade. In our study, similar to the literature findings, there was no significant correlation between the presence of neuropathic pain, age, and symptom duration.…”
Section: Discussionmentioning
confidence: 95%
“…High PainDETECT scores in patients with OA have been shown to be associated with impaired quality of life [34]; whereas Hochman et al [30] noted a significant association between depression and neuropathic pain in patients with knee OA. In addition, in patients with neuropathic pain as determined with PainDETECT scale, Mesci et al [35] found higher WOMAC and HAD anxiety–depression scores and lower scores from the SF‐36. In our study, the difference was not statistically significant; although, we found higher HAD anxiety–depression scores among patients with neuropathic pain that were determined with PainDETECT compared with patients without neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Именно при ОА КС предлагается использование психометрических тестов [31]. Такие пациенты нередко яв-ляются объектом для изучения нейропатической боли [32,33], чаще всего в этих случаях рассматриваются перекрест-ные связи в триаде «нарушения сна -боли -депрессия» и предполагается уникальная предсказательная роль ком-понентов этой триады, индуцирующих друг друга по «по-рочному кругу» в развитии инвалидности, и высокая зна-чимость этих факторов для разработки ее профилактики [34,35]. Изучение тяжести инсомний, качества сна и по-следствий его нарушения у пожилых лиц с ОА КС показа-ло, что индивидуальные убеждения в отношении сна игра-ют даже большую роль, чем депрессия и боль, а в качестве наилучшего предиктора его нарушений выступает не столько депрессия, сколько такой симптом, как утомляе-мость [36], который хотя и не столь специфичен, но, как известно, сам по себе является одним из основных призна-ков депрессии.…”
unclassified